The Effect of Human Resource Management Management, To Performance Through Innovation Organization - M. C. Sina Setyadi (International Conferences SDGs 2030 Challenges and Solutions, 2030)
This study aims to describe human resource management practices, organizational innovation and organizational performance, analyze the effect of HR management practices on organizational innovation, analyze the influence of HR management practices on organizational performance, analyze the influence of organizational innovation on organizational performance, and analyze the impact of HR management practices on performance Organization through organizational innovation. This study included research to test the hypothesis (hypothesis testing). The sample in this research is 140 companies. The analytical technique using Structural Equation Modeling. Based on the results of the analysis shows that the practice of human resource management has an impact on organizational innovation. The practice of human resource management is concerned with organizational performance. Organizational innovation affects organizational performance. Organizational innovation mediates the impact of human resource management practices on organizational performance.